Evaluation of The Effectiveness of Watershed Rehabilitation in West Lombok District - Soumena, Welmy; Sjah, Taslim; Hayati, Hayati (Jurnal Biologi Tropis, 2026)
The watershed (DAS) in West Lombok Regency has experienced environmental degradation due to land-use conversion and unsustainable agricultural practices in upstream areas, resulting in increased critical land, erosion, and declining hydrological functions. This study aimed to evaluate the effectiveness of watershed rehabilitation programs, assess their impacts on vegetation recovery, identify factors influencing program success, and formulate sustainable management strategies. A mixed-methods approach was employed. Quantitative analysis utilized Geographic Information System (GIS)-based remote sensing, applying the Normalized Difference Vegetation Index (NDVI) to assess vegetation cover and the Universal Soil Loss Equation (USLE) to estimate erosion levels. Qualitative data were collected through field observations and semi-structured interviews to evaluate community participation, institutional support, and implementation constraints. The results showed that watershed rehabilitation improved environmental conditions, as indicated by increased vegetation density, expanded canopy cover, and reduced critical land areas. The use of multipurpose tree species (MPTS), including mahogany, sengon, durian, and candlenut, was well adapted to local conditions and provided additional economic benefits through agroforestry practices. Plant survival rates were generally moderate to high. However, program effectiveness was constrained by limited maintenance funding, seasonal water shortages, livestock disturbances, and weak monitoring systems. Strong community participation and local institutional support were associated with better rehabilitation outcomes. This study concludes that integrating vegetative and mechanical conservation measures with community-based economic empowerment is essential for enhancing watershed rehabilitation effectiveness and sustaining hydrological ecosystem functions in West Lombok Regency.